DEVELOPMENT OF BORDER AREAS AS A GOOD AND PROUD FRONT YARD - Widia Novita Lukitasari WA (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2026)
Border area development constitutes one of Indonesia's national strategic priorities as it is closely related to national sovereignty, security, equitable regional development, and community welfare. Nevertheless, border regions continue to face numerous challenges, including limited infrastructure, inadequate education and healthcare services, geographical isolation, and the underutilization of natural resource potential. This paper aims to analyze border area development as the